Contribution of anxiety and dialysis factors to the event of fatigue in hemodialysis patient - Yanti Cahyati; Ida Rosdiana (Enfermería Nefrológica, 2022)
Introduction: Fatigue is one of the most common symptoms felt by chronic renal failure patients undergoing hemodialysis (HD). The prevalence ranges from 42-97% with levels varying from low to severe. Fatigue is not only detrimental to physical and social functioning but is also associated with poor quality of life for HD patients and is associated with death in patients undergoing chronic hemodialysis. For this reason, it is necessary to know the factors associated with the incidence of fatigue so that appropriate interventions can be carried out, both pharmacologically and non-pharmacologically. Objective: To evaluate the influence of anxiety and dialysis factors on the incidence of fatigue in patients undergoing hemodialysis at Ciamis Hospital. Material and Method: A cross sectional approach with a total sample of 88 people was used. Results: The results showed that 78 respondents (88.6%) who experienced fatigue complaints and anxiety had a relationship with the incidence of fatigue (OR: 9.0; p=0.019). Conclusions: Psychological factors, such as anxiety, are associated with the fatigue experienced by patients on hemodialysis.